(untitled) (Research, Society and Development, 2021)
Objective: To promote reflections on comprehensive nursing care from the perspective of Martha Elizabeth Rogers Theory and the contact of babies with their mothers and the nursing staff. Methodology: This is an article of theoretical-reflective analysis supported by the theoretical framework of the theory of Martha Elizabeth Rogers, for which a search was carried out for productions that dealt with the topic in Academic Google and Pubmed, based on the experience of two experienced nurses in neonatal care, which occurred in June and July 2021. Results: In care practice in neonatology, touch benefits the baby’s development and during this contact it is possible to soften the negative feelings and promote a positive relationship with the child through the exchange of energy with the mother and the nursing team, this way two-way approach contemplates the core components of Rogers’ Science of Unitary Human Beings. Final considerations: This reflection contributed to a better understanding of the empirical knowledge about: touch, energy fields, the baby, the mother, the nursing team, Rogers’ theory, which together with the theoretical framework, shows how important the topic is, current and through it new concepts can be developed.